Behavior of dissolved organic carbon sources on the microbial reduction and precipitation of vanadium(v) in groundwater. Issue 99 (11th October 2016) - Liu, Hui; Zhang, Baogang; Xing, Yi; Hao, Liting
Abstract : The performance of anaerobic microbial vanadium(v ) reduction using five ordinary dissolved organic carbon sources was evaluated. Abstract : The performance of anaerobic microbial vanadium(v ) reduction using five ordinary dissolved organic carbon sources was evaluated. In general, V(v ) removal efficiency decreased with an increase in the molecular weight of the carbon substrate. In addition, organic acids supported a higher V(v ) removal than alcohols, thus achieving the highest V(v ) removal efficiency of 75.6% using acetate during a 12 h operation, compared with lactate, glucose, citrate and soluble starch. A higher initial V(v ) concentration led to a lower V(v ) removal efficiency, while the extra addition of organics had little effect on its improvement. With an increase in the pH and conductivity, the V(v ) removal efficiency first increased and then decreased. High-throughput 16S rRNA gene pyrosequencing analysis indicated the accumulation of Actinobacteria, Chlorobaculum of Chlorobi and Proteiniphilum of Bacteroidetes, which might be responsible for the function of the proposed system. This study provides a step forward for the remediation of V(v ) from polluted groundwater, by employing a promising biotechnology.